ON ENVIRONMENTAL CONTAMINATION DURING OIL AND GAS WELLS DRILLING - KURHANSKYI, V.; TISHAIEV, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The sources of environmental contamination in drilling process of oil and gas wells are considered. The general tasks for oil-andgas geoecology are defined.